Type D personality, suboptimal health behaviors and emotional distress in adults with diabetes: Results from Diabetes MILES–The Netherlands. Issue 1 (April 2015) - Nefs, G.; Speight, J.; Pouwer, F.; Pop, V.; Bot, M.; Denollet, J.
Abstract Aims Type D personality – defined as high negative affectivity (NA) and high social inhibition (SI) – has been associated with adverse cardiovascular prognosis. We explored the differential associations of Type D personality and its constituent components with health behaviors, emotional distress and standard biomedical risk factors as potential risk mechanisms in adults with diabetes. Methods 3314 Dutch adults with self-reported type 1 or 2 diabetes completed an online survey, including the DS14 Type D Scale. AN(C)OVAs and X2 tests were used to compare participants scoring (i) low on NA and SI; (ii) high on SI only; (iii) high on NA only; (iv) high on NA and SI (Type D). Results Participants with Type D personality (29%) were less likely to follow a healthy diet or to consult healthcare professionals in case of problems with diabetes management than those scoring high on neither or only one component. They also reported more barriers surrounding medication use, diabetes-specific social anxiety, loneliness and symptoms of depression and anxiety. There were no differences in standard biomedical risk factors (body mass index, blood pressure, cholesterol, HbA1c). After adjustment for demographics, clinical characteristics, NA, and SI in multivariable logistic regression analyses, Type D personality was independently associated with 2 to 3-fold increased odds of suboptimal health behaviors and over 15-fold increased odds of general emotional distress. Conclusions Type D personality was not related to standard biomedical risk factors, but was associated with unhealthy behaviors and negative emotions that are likely to have adverse impact on adults with diabetes.